AH-39 Lingual Gland Morphology of the Female Swiflet (Collocalia linchi) During Productive and Nesting Periods - Savitri Novelina; Rany Puspa Pijayanti; Heru Setijanto (Media Veteriner, 2015)
Lingual Gland Morphology of the Female Swiflet (Collocalia linchi) During Productive and Nesting Periods